A new endemic species of Manihot (Euphorbiaceae s. str.) from the Chapada dos Veadeiros, Goiás, Brazil - Da Silva, Marcos José; Sodré, Rodolfo Carneiro; Almeida, Laura Cristina Da Silva (Phytotaxa, 2013)
A new species from the grasslands of the Chapada dos Veadeiros, Manihot kalungae, is described and illustrated herein. Based on morphological traits, the narrowly endemic species is proposed to belong to Manihot sect. Peltatae, a remarkable group of the genus due to the peculiar morphology of the leaves. A key to the species of Manihot sect. Peltatae is provided.